2022
DOI: 10.1001/jamadermatol.2022.0001
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Satellitosis or In-transit Metastasis in Cutaneous Squamous Cell Carcinoma

Abstract: cell carcinoma and melanoma, satellitosis or in-transit metastasis (S-ITM) is not incorporated into the current cutaneous squamous cell carcinoma (CSCC) staging systems. It is important to determine if the clinical outcomes of S-ITM are relevant to prognosis for patients with CSCC.OBJECTIVES To evaluate the association of S-ITM with clinical outcomes in patients with CSCC and to determine its prognostic implications. DESIGN, SETTINGS, AND PARTICIPANTSA dual-institution (Cleveland Clinic and Brigham and Women's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Recent studies have demonstrated that cSCC patients with in-transit metastases have clinical outcomes similar to those who are node-positive, and may be useful for prognostication. 5 Given the similar or greater aggressiveness and poor outcomes of EPC compared with cSCC, identification of in-transit metastases may warrant prognostic and management approaches similar to those for nodal metastases. The potential for EPC satellite lesions to affect management highlights the importance of thorough skin examination, as in this case, and suggests that their presence or absence should be reflected in future staging systems or consensus guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that cSCC patients with in-transit metastases have clinical outcomes similar to those who are node-positive, and may be useful for prognostication. 5 Given the similar or greater aggressiveness and poor outcomes of EPC compared with cSCC, identification of in-transit metastases may warrant prognostic and management approaches similar to those for nodal metastases. The potential for EPC satellite lesions to affect management highlights the importance of thorough skin examination, as in this case, and suggests that their presence or absence should be reflected in future staging systems or consensus guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…For skin cancers, predictive risk estimates remain poor and staging systems remain inadequate 19,62,71 . In consequence, aggressive biologic behaviour often goes unrecognised.…”
Section: Assessing Distal Metastatic Riskmentioning
confidence: 99%
“…For skin, these include all intradermal or subdermal metastasis between the primary scar and the tumour-draining nodal basin. 26,[61][62][63] Macrometastatic ITM present as papulo-nodules and are described for SCC, 40,62,64 MCC 26,27 and melanoma. 58,61,[65][66][67][68] As external assay techniques improve in sensitivity, it is expected that smaller mass cancer cell clusters will be identified in lymphatic channels.…”
Section: Early Detection Of Micrometastasesmentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma (CSCC) is the second most common keratinocyte carcinoma in the US, with an estimated 700 000 to 1 000 000 cases reported annually . While most patients with CSCC are cured with Mohs micrographic surgery (Mohs) or wide local excision (WLE) alone, a subset of patients go on to develop poor outcomes, including local recurrence (LR), nodal metastasis (NM), distant metastasis (DM), and disease-specific death (DSD) .…”
Section: Introductionmentioning
confidence: 99%
“…utaneous squamous cell carcinoma (CSCC) is the second most common keratinocyte carcinoma in the US, with an estimated 700 000 to 1 000 000 cases reported annually. 1,2 While most patients with CSCC are cured with Mohs micrographic surgery (Mohs) or wide local excision (WLE) alone, a subset of patients go on to develop poor outcomes, including local recurrence (LR), nodal metastasis (NM), distant metastasis (DM), and disease-specific death (DSD). [3][4][5][6][7] Current staging systems such as the American Joint Committee on Cancer's AJCC Cancer Staging Manual, 8th edition (AJCC-8) and the Brigham and Women's Hospital (BWH) staging system are based on tumor characteristics that have been shown to impact prognosis.…”
mentioning
confidence: 99%